Modeling of Microwave Semiconductor Diodes - Pokorny, Michal; Raida, Zbynek (Společnost pro radioelektronické inženýrství, 2008)
The paper deals with the multi-physical mode-ling of microwave diodes. The electrostatic, drift-diffusion and thermal phenomena are considered in the physical model of the components. The basic semiconductor equati-ons are summarized, and modeling issues are discussed. The simulations of the Gunn Effect in transferred electron devices and the carrier injection effect in PIN diodes are investigated and discussed. The analysis was performed in COMSOL Multiphysics using the finite element method.
Keywords: Gunn effect; carrier injection effect; PIN; FEM; COMSOL Multiphysics; drift-diffusion scheme; multi-physical model